Measuring treatment effects in poverty alleviation programs: three essays using data from Turkish household surveys - Aran, M (2012)
The dissertation is a compilation of three essays on Turkey's poverty alleviation programs. The first paper focuses on the welfare impact of the global financial Crisis on Turkish households. The second paper considers the protective impact of the Green Card non-contributory health insurance program in Turkey during the Crisis in 2008-2009. The third paper uses experimental data from the field in eastern Turkey, to look at patterns of agricultural technology diffusion in a rural development program implemented in a post-conflict setting.